The value of real world evidence: The case of medical cannabis - Schlag, Anne Katrin; Zafar, Rayyan R.; Lynskey, Michael T.; Athanasiou-Fragkouli, Alkyoni; Phillips, Lawrence D.; Nutt, David J. (Frontiers in Psychiatry, 2022)
Randomised controlled trials (RCTs) have long been considered the gold standard of medical evidence. In relation to Cannabis based medicinal products (CBMPs), this focus on RCTs has led to very restrictive guidelines, which are limiting patient access to the medicine in the UK. There is general agreement that RCT evidence in relation to CBPMs is insufficient at present. As well as commercial reasons a major problem is that RCTs do not lend themselves well to the study of whole plant medicines. One solution to this challenge is the use of Real World Evidence (RWE) with Patient Reported Outcomes (PROs) to widen the evidence base. Such data increasingly highlights the positive impact medical cannabis can have on patients’ lives. This paper outlines the value of this approach which involves the study of interventions and patients longitudinally under medical care. In relation to CBMPs, RWE has a broad range of advantages. These include the study of larger groups of patients, the use of a broader range and ratio of components of CBMPs, and the inclusion of more and rarer medical conditions. Importantly in contrast to RCTs patients with significant comorbidities – and from a wider demographic profile - can also be studied, so providing higher ecological validity and increasing patient numbers, whilst offering significant cost savings. We conclude by outlining 12 key recommendations of the value of RWE in relation to medical cannabis. We hope that this paper will help policymakers and prescribers understand the importance of RWE in relation to medical cannabis and help them develop approaches to overcome the current situation which is detrimental to patients.